Pengembangan Media Pembelajaran Pop-Up Book Pada Muatan Pembelajaran IPS Kelas IV SDN 07 Kota Bima Tahun Ajaran 2021/2022 - Qurrata A’yun; Nurhasanah Nurhasanah; Moh Irawan Zain (Journal of Science Instruction and Technology, 2021)
The aim of this study is to produce products and find out the feasibility of the media pop-up book that has been developed. The research methods were the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation) and with R&D (Research and Development) research design or known as research and development conducted by a teacher and 6 learners in SDN 07 Bima City. The object of this research is a media pop-up book IPS (Social Science) content, theme "A proud of my environment". Subtema "The area where I live". In the results of research validators, pop-up book media material expert got very valid criteria with a score of 84%, from the validator of media experts in the pop-up media book get very valid criteria with a score of 97%, the assessment of 6 learners against the media pop-up book got very valid criteria with a score of 92%. Thus, the media pop-up book IPS (Social Science) content above gets the criteria is very valid so that the results of the development of pop-up book media are worth using in class IV elementary school.